TOWARDS A BIBLICAL THEOLOGY OF RELIGION FOR THIS TIME: CRUX AND POSSIBILITIES - Dirk Griffioen (Phronesis: Jurnal Teologi dan Misi, 2020)
In this article I point out that a reformed or practical biblical theology of religion still needs to adapt to our contemporary era. In order to achieve that this research makes use of the efforts made by other people. I am going to focus on the central problem - the questions which I think pertain to religious theology. In the past much attention has been given among us to theological questions but not much has been done to build a system. Hendrik Kraemer was the first missionary to develop a more or less comprehensive theology of religion. One of the results of this research shows that Religion and religions, Christianity and non-Christianity, are phenomena and / or institutions that must be described, compared, and assessed.